The COVID-19 Pandemic and Breastfeeding: Concerns & Positive Opportunities. Issue 4 (July 2021) - Spatz, Diane L.
Abstract : As nurses, we must continue to promote and protect the use of human milk and breastfeeding during and after the COVID-19 pandemic. We should continue access to online and virtual breastfeeding help but expand opportunities for in-person technical breastfeeding assistance in pediatric offices and in the community. Our breastfeeding expert, Dr. Spatz, offers suggestions for promoting breastfeeding during the pandemic and beyond.